Crankshaft high cycle bending fatigue test method based on the combined extended Kalman filtering algorithm and different failure criterion parameters - Zhang Wei; Yan Ruidong; Songsong Sun; Gong Xiaolin; Liu Zhentao (PLoS ONE, 2025)
In this paper, an accelerated bending fatigue test method for the crankshaft was proposed based on the combination of the extended Kalman filtering algorithm method (EKF) and different failure criterion parameters. First the intrinsic frequency of the system and the fatigue crack depth were chosen to be the failure criterion parameters based on the test regulation and the theory of fracture mechanics. Then the extended Kalman filtering method was adopted in predicting the remaining high cycle fatigue life of the crankshaft during the experiment process. Finally the predicted fatigue life was selected to replace the actual test results for the key fatigue property parameter analysis. Based on this research, the time duration of the test was reduced obviously without affecting the key analysis parameters obviously. In addition, compared with the intrinsic frequency of the system, the fatigue crack depth is more suitable to be selected as the failure criterion to provide more reasonable enhancing effect. The main conclusions draw from this paper can provide some theoretical guidance for the design and manufacturing process of the part.